(2R,6R)-Hydroxynorketamine is not essential for the antidepressant actions of (R)-ketamine in mice - Yamaguchi, Jun-ichi (Neuropsychopharmacology, 2018)
(R,S)-Ketamine has rapid and sustained antidepressant effects in depressed patients. Although the metabolism of (R,S)-ketamine to (2 R,6 R)-hydroxynorketamine (HNK), a metabolite of (R)-ketamine, has been reported to be essential for its antidepressant effects, recent evidence suggests otherwise. The present study investigated the role of the metabolism of (R)-ketamine to (2 R,6 R)-HNK in the antidepressant actions of (R)-ketamine. Antidepressant effects were evaluated using the forced swimming test in the lipopolysaccharide (LPS)-induced inflammation model of mice and the tail suspension test in naive mice. To prevent the metabolism of (R)-ketamine to (2 R,6 R)-HNK, mice were pretreated with cytochrome P450 (CYP) inhibitors. The concentrations of (R)-ketamine, (R)-norketamine, and (2 R,6 R)-HNK in plasma, brain, and cerebrospinal fluid (CSF) samples were determined using enantioselective liquid chromatography-tandem mass spectrometry. The concentrations of (R)-norketamine and (2 R,6 R)-HNK in plasma, brain, and CSF samples after administration of (R)-norketamine (10 mg/kg) and (2 R,6 R)-HNK (10 mg/kg), respectively, were higher than those generated after administration of (R)-ketamine (10 mg/kg). Nonetheless, while (R)-ketamine attenuated, neither (R)-norketamine nor (2 R,6 R)-HNK significantly altered immobility times of LPS-treated mice. Treatment with CYP inhibitors prior to administration of (R)-ketamine increased the plasma levels of (R)-ketamine, while generation of (2 R,6 R)-HNK was almost completely blocked. (R)-Ketamine exerted the antidepressant effects at a lower dose in the presence of CYP inhibitors than in their absence, which is consistent with exposure levels of (R)-ketamine but not (2 R,6 R)-HNK. These results indicate that metabolism to (2 R,6 R)-HNK is not necessary for the antidepressant effects of (R)-ketamine and that unmetabolized (R)-ketamine itself may be responsible for its antidepressant actions.